Adsorptive removal of thiophene by using water based silver nanofluid. (15th February 2023) - Khidr, Amal S.A.; Soliman, F.S.; Zaki, T.; Sabry, D.Y; Al-Sabagh, A.M.
Graphical abstract: Highlights: Silver nanofluids were synthesized and characterized. The silver nanoparticles, of size 8.3 nm, showed the highest adsorption efficiency. After thiophene adsorption, silver nanoparticles become amphiphilic. Amphiphilic silver nanoparticles form ultrathin film at the oil water interface. Abstract: In this work, a simple, eco-friendly, and energy-efficient protocol was used for the removal of thiophene as a model for the sulfur compounds present in gasoline. The water-based silver nanofluid was prepared via the chemical reduction method, using tannic acid as both a reducing and stabilizing agent. The prepared silver nanoparticles (AgNPs) were characterized using X-ray diffraction (XRD), dynamic light scattering (DLS), ultraviolet–visible spectroscopy, and transmission electron microscope (TEM). For studying the adsorption efficiency of the silver nanoparticles, several parameters were evaluated, such as the contact time, the size and stability of the nanoparticles, the concentrations of AgNPs, and the thiophene. The silver nanoparticle, of size 8.3 ± 2 nm, showed the highest adsorption efficiency (i.e., 88.4 %) from thiophene solution (500 ppm) (190.5 ppm S). The adsorption process underwent a pseudo-second-order. Furthermore, the adsorption mechanism was studied. The results could be attributed to the partially replacing of the capping agent, i.e., tannic acid, with thiophene, which is considered a hydrophobic agent, during the agitation process. Accordingly, the silver nanoparticle, contaminated with sulfur compounds, spontaneously migrated to the oil/water interface. AgNPs capped with thiophene were characterized using field emission-scanning electron microscope (FE-SEM), transmission electron microscope (HR-TEM), EDX-mapping, and dispersive Raman microscope. This approach provides a new way to remove thiophene by using the aqueous fluid of silver nanoparticles.